EPR detection of sphalerite ZnO in mechanically treated ZnO+0.1C nanosystem - Kakazey, M.; Vlasova, M.; Juárez Arellano, Erick Adrián; Torchynska, T. (Elsevier Ltd., 2015)
The EPR spectrum of Mn2+ ions observed in nano-powders of wurtzite ZnO phase (ZnOWt) with 0.1 wt% of carbon nanoparticles subjected to mechanical processing (MP) for tMP>90 min where different than the well-known EPR spectrum of Mn2+ in ZnOWt. Such spectrum was observed earlier and it was attributed to either a new phase or a highly disordered nanocrystalline ZnOWt. Spin–Hamiltonian (S–H) parameters and line width (ΔB) have been determined by computer simulation of observed EPR spectrum of Mn2+: g=2.0010±0.0004, |A|=(73.6 ±0.3)·10−4 cm−1, |D|=(102 ±30)·10−4 cm−1, ΔB≈0.6 mT. The comparison of S–H parameters of the EPR spectra of Mn2+ ions in a new formed phase and in ZnOWt indicates that the parameter A of the hyperfine structure in a new phase is slightly smaller and that the D parameter is more than two times lower than in ZnOWt. The content of the newly formed phase (~1% to 2%) is significantly higher than the content of external impurity states in the initial ZnO sample. The observed EPR spectrum is attributed to the Mn2+ ions in the zinc blende (sphalerite) ZnO phase (ZnOZB), created on the surface of ZnOwt nanoparticles during mechanical processing.
Keywords: Procesamiento mecánico